Ewing-s Sarcoma of the Peritoneum: a Rare Location for Extraskeletal Ewing-s Sarcoma - SAĞLAM, MUZAFFER; Saglam, MUZAFFER; OZDEMIR, Yavuz; YIGIT, Taner; KUCUKODACI, Zafer; SONMEZ, Guner (My University, 2016)
A 38-year-old male presented to the emergency department with abdominal pain and bulge. He had a history of irritable bowel syndrome for 1 year with complaint of dyspepsia. Physical examination revealed a distended abdomen with a huge palpable mass located in the paraumblical region. Laboratory findings revealed a high white blood cell count with neutrophil predominance. Contrast-enhanced computed tomography (CT) showed a 23-cm, oval-shaped, grossly necrotic, low-attenuation mass with peripherally located dominant vessels. Magnetic resonance imaging (MRI) with diffusion weighted imaging (DWI) suggested a highly malignant tumor with prominent diffusion restriction especially at the periphery of the mass. On surgery, macroscopic examination showed a macrolobulated, hypervascular, reddish brown mass attached to the parietal peritoneum with a stalk. Ewing-s sarcoma (ES) was diagnosed on histopathological examination with small round cells.